Servant Leadership Training for Leaders and Teachers of SMK Pasundan in Bandung and Cimahi City - Rustandi, Iyus; Aripin, Yusuf (Bulletin of Community Engagement, 2024)
The principal of a school is expected to implement a strategy that will enable the school to provide education services of an appropriate quality, in accordance with the standards set by the national level. In order to achieve this, the principal must be able to mobilize the human resources of the organization, which includes educators, school employees, and students. In order to do this, the principal must adopt a leadership style that is suitable for an educational institution, which is known as servant leadership. This research was conducted with a qualitative approach. The research method employed an interview with the principal as the respondent. The responses from this individual were considered as individual opinions and then aligned with the theoretical studies derived from the literature data. In order to substantiate this data, the results were subjected to data reduction techniques, namely analyzing, selecting and discarding in order to reach conclusions that could be verified. The results demonstrated that there were six distinct servant leadership models, namely: The six characteristics of servant leadership are as follows: value people, develop people, build community, display authenticity, provide leadership, and share leadership. The five servant leadership values are as follows: listening, fulfilling, empathy, healing, self-awareness, persuasion, and conceptualization Keywords : Servant Leadership Training, Servant Leadership